Euthynnus affinis - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Euthynnus affinis (Cantor, 1849). Kawakawa or Mackerel Tuna. To 110 cm (43.3 in) TL (Robertson and Allen 2002). Indo-Pacific; western Pacific Ocean north to southern Japan (Nakabo in Nakabo 2002); near Diablo Cove, central California (Jay Carroll, pers. comm. to M.L.), and Los Angeles Harbor, southern California (Miller and Lea 1972), and off southern Baja California (Robertson and Allen 2008) and Islas Revillagigedo (Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California). Neritic epipelagic; depth: surface to 73 m (164 ft) (Robertson and Allen 2002). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 211, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008